Messaging System Design Based on Using Servers and Encoding System - Musbah Joma Aqel (International Journal of Interactive Mobile Technologies, 2020)
Now, people all over the world use messengers to communicate with their families and employees at work, schedule meetings, congratulate on holidays, and conduct banking operations using bots built into messengers. However, it is challenging to improve such architectures, as a result of which WhatsApp still does not have Chabot’s, whereas their competitors from Telegram already have them built-in. The essence of this project is to create a messenger that has an optimal ratio of functionality and code processing speed, as well as the ability to improve the architecture without high resource costs quickly. The basic version has features such as registration, logging in with your account, checking whether the user is online, messaging, and hash encoding for secure messaging over the Internet. The result showed a high potential for improving the application architecture in any part of the code within the acceptable level of influence on its other functions, as well as a more stable operation of the application itself in comparison with applications built based on Android or JavaScript. However, it was not possible to achieve a higher code processing speed in comparison with other Android or web applications. A method is designed and implemented to enhance the speed of code processing. The results produced by this proposed method and design has shown enhancement in the speed of code processing for messengers. Compared with other Android or with other web applications messaging systems.